In Silico Analysis on the Interaction of Haloacid Dehalogenase from Bacillus cereus IndB1 with 2-Chloroalkanoic Acid Substrates - Enny Ratnaningsih; Saepulloh Saepulloh (The Scientific World Journal)
Recently, haloacid dehalogenases have gained a lot of interest because of their potential applications in bioremediation and synthesis of chemical products. The haloacid dehalogenase gene from Bacillus cereus IndB1 (bcfd1) has been isolated, expressed, and Bcfd1 enzyme activity towards monochloroacetic acid has been successfully studied. However, the structure, enantioselectivity, substrate range, and essential residues of Bcfd1 have not been elucidated. This research performed computational studies to predict the Bcfd1 protein structure and analyse the interaction of Bcfd1 towards several haloacid substrates to comprehend their enantioselectivity and substrates’ range. Structure prediction revealed that Bcfd1 protein consist of two domains. The main domain consists of seven β-sheets connected by six α-helices and four 310-helices forming a Rossmannoid fold. On the other hand, the cap domain consists of five β-sheets connected by five α-helices. The docking simulation showed that 2-chloroalkanoic acids bind to the active site of Bcfd1 with docking energy decreases as the length of their alkyl chain increases. The docking simulation also indicated that the docking energy differences of two enantiomers of 2-chloroalkanoic acids substrates were not significant. Further analysis revealed the role of Met1, Asp2, Cys33, and Lys204 residues in orienting the carboxylic group of 2-chloroalkanoic acids in the active site of this enzyme through hydrogen bonds. This research proved that computational studies could be used to figure out the effect of substrates enantiomer and length of carbon skeleton to Bcfd1 affinity toward 2-chloroalkanoic acids.